Patents for All: A Content Analysis of an Open-access Dataset of Colombian Patents 1930–2000 (2019)
The production of knowledge stock is essential for the long-term growth of a nation. One component of knowledge stock is patents. The publication of patents, nevertheless, is unevenly distributed around the world. To better understand these inequalities in the context of a developing country such as Colombia, it is crucial to integrate historical insights into institutions and economic outputs. Despite this need, peer-reviewed literature on the history of patents in Colombia is scarce. In this context, we look at a barely known or cited work entitled Inventos y patentes en Colombia 1930–2000, published by Alberto Mayor in 2005. He recorded more than 1500 patents granted between 1930 and 2000. Using this historical dataset, we discuss the historical pathway regarding the publication of patents and inventions in Colombia between 1930 and 2000 by identifying critical factors such as patent registration by year, coefficient of invention, type of inventor (male, female, group of inventors, or a company), geographical location, classification, and a content analysis of the text corpus of the patent titles.